Engineering mechanics - Meriam, J. L. (James L.); Kraige, L. G. (L. Glenn) (Hoboken, NJ : Wiley, 2007)
Over the past 50 years, Meriam and Kraige's Engineering Mechanics has established a highly respected tradition of excellence. Readers turn to this book because of its emphasis on accuracy, rigor, clarity, and applications. The new sixth edition continues this tradition while also improving the accessibility of the material.
v. 1. Statics -- volume 2. Dynamics.
Includes index.
Keywords: Mechanics, Applied